Syngas production from microwave gasification of oil palm biochars - Ismail, Norasyikin (2015)
Gasification is a reaction process between solid or liquid carbonaceous materials with some gasifying agent to produce gaseous fuel. In this study, a microwave gasification test rig is designed to produce syngas from oil palm biochars. Carbon dioxide is used as the gasifying agent. Oil palm empty fruit bunch (EFB) and oil palm shell (OPS) biochars are used as the carbonaceous materials. The effects of CO2 flow rates on the type of biochars to the syngas produced are investigated. The optimum CO2 flow rate for EFB biochar gasification is 3 lpm where the gas compositions are 0.52% CH4, 50.52% CO2, 26.1% CO, and 22.86% H2. For OPS biochar, the optimum CO2 flowrate is 2 lpm that produce 6.92% CH4, 57.19% CO2, 10.98% CO, and 24.92% H2. For EFB biochar gasification, the specific volume of gas yield is from 1.22 to 1.51 m3/kg while for OPS biochar yields higher specific gas volume, ranging from 2.62 to 7.88 m3/kg. The highest carbon conversion efficiency and gas heating value for EFB biochar is 75.07% and 12.84 MJ/kg at 3 lpm respectively and 66.83%, 13.03 MJ/kg at 2 lpm for OPS biochar respectively . This concludes that EFB biochar produced higher quality syngas than OPS biochar because of the higher volume of CO and H2 content in the syngas produced at the higher carbon conversion efficiency with specific gas volume of 1.22 m3/kg.